Queer Narrative, Aesthetic, and Political Experience in the Struggle for Peace: Notes on the Short Film Negrum3 - de Barros, Laan Mendes; Wlian, Luiz Fernando [UNESP] (Universidad de los Andes, 2023)
| The contemporary Brazilian context offers a growing artistic and cultural production, generated by LGBTQIA+ subjects, which disputes narratives and sensitivity, and suggests new ways of being in the social world. This article looks at how such artistic-cultural production can bring critiques and contributions on peacebuilding. The article questions how to think peacebuilding from queer perspectives: it confronts peacebuilding with dissident critiques, in order to think a possible idea of queer peace. This is proposed through the aesthetic experience, in articulations between affection and politics that mobilize relations of recognition and otherness, from a sensitive perception of the discourses of resistance and affirmation of existence. To conduct an analysis that values culture —and its aesthetic and sensitive character— as a relevant field for research in the social and political sciences, we discuss the short film Negrum3 by filmmaker Diego Paulino. This audiovisual object is analyzed through a brief historical incursion, which presents a picture of LGBTQIA+ public policies in Brazil and their possible bridges with an idea of peacebuilding, and a theoretical reflection that contrasts decolonial theories with figures from the European academia. Thus, we reflect on how a queer peace can be built in the dimension of aesthetic experience, which is also political, and allows us to imagine and enable new forms of life. Our conclusion is that queer peace is a challenging conception, which retains its challenges and is based on a critique of hegemonic and institutionalized apprehensions of peace. In this sense, the artistic-cultural production, with its aesthetic approaches, appears as an inventive path. The originality of the article consists in its articulation of queer theories and, above all, of aesthetic and political practices, to think about peacebuilding in Brazil's social reality.
Narrativa cuir, experiencia estética y política en la lucha por la paz: apuntes sobre el cortometraje Negrum3
Narrativa cuir, experiência estética e política na luta pela paz: notas sobre o curta-metragem Negrum3
Keywords: aesthetic experience; Brazil; otherness; peacebuilding, queer peace